A Research Protocol and Case Report of Emergency Department Endovascular Aortic Occlusion (REBOA) in Non-traumatic Cardiac Arrest - Daley, James; Cannon, Kathryn; Buckley, Ryan; Aydin, Ani; Latich, Igor; Lozada, Juan Carlos Perez; Bonz, James; Joseph, Daniel; Coughlin, Ryan; Belsky, Justin; Van Tonder, Reinier; Sather, John; et al. (Journal of Endovascular Resuscitation and Trauma Management, 2020)
Background: There are over 395,000 out-of-hospital cardiac arrests (OHCA) annually in the United States with an estimated 70–90% mortality rate and fewer than 10% surviving with a favorable neurologic outcome. Research in animal models and early human studies suggests that resuscitative endovascular balloon occlusion of the aorta (REBOA) may play a role in augmenting coronary perfusion during OHCA by reducing blood flow to the lower body and re-directing it towards the heart and the brain. We describe our initial case and research protocol to investigate the feasibility of REBOA in the emergency department for OHCA as an adjunct to advanced cardiac life support. Methods: We plan to enroll 20 patients in a single-arm interventional device study utilizing an exception from informed consent over a 2-year period. The primary outcome is feasibility, with secondary outcomes assessing for hemodynamic changes pre- and post-aortic occlusion. Results: Enrollment began in January 2020 and is ongoing. For the initial patient, an emergency physician (EP) obtained common femoral arterial access under chest compressions, followed by advancement of the REBOA catheter by an interventional radiologist. Immediately after aortic occlusion, investigators noted a substantial improvement in mean arterial pressure (37 mmHg to 50 mmHg) and end tidal carbon dioxide (33 mmHg to 50 mmHg), with transient but non-sustained return of spontaneous circulation. Conclusion: This is the first research protocol and case report describing successful REBOA placement in the emergency department (ED) involving EPs for non-traumatic OHCA as an adjunct to advanced cardiac life support.